ATM germline variants and male breast cancer. Issue 1 (18th January 2021) - Cunha, Renato; Nejo, Priscila; Bento, Sandra; Vaz, Fátima
Abstract : Male breast cancer is rare and has been frequently associated with cancer predisposing variants, particularly in BRCA 1 and BRCA 2 genes. ATM pathogenic variants may also increase risk for breast and other cancers. However, less than 10 cases relating ATM mutations and male breast cancer have been previously reported. Therefore, risk estimates and surveillance recommendations are not well established. We report a case of a male patient with breast cancer found to be heterozygous for a pathogenic ATM variant after multigene testing. We also review the literature regarding increased cancer risk associated with ATM germline variants, with emphasis on potential recommendations for surveillance and follow-up.